Driving mechanism of green supply chain integration on green innovation under environmental uncertainty: Mediating role of knowledge sharing - Zhu, Lidi (Edelweiss Applied Science and Technology, 2025)
Traditional approaches to promoting green innovation (GI) have problems such as isolated local innovation, lack of collaboration and systematization, and excessive focus on short-term benefits. This paper proposes using the mediating role of knowledge sharing (KS) to influence green supply chain integration (GSCI) with environmental uncertainty (EU) factors, thereby promoting the realization of GI. Through this integration, the problems of isolated innovation and short-term benefit orientation in traditional methods are solved, and GI’s collaborative and systematic development is promoted. Firstly, a questionnaire on the effect of GSCI is designed, and then descriptive statistical analysis is used to understand the basic situation of GSCI and related control variables. Multiple linear regression is used to test whether GSCI can affect GI, and mediation effect analysis is then used to test whether KS can play a mediating role. Finally, interaction regression analysis is used to explore whether the EU can moderate the impact of GSCI on GI. In the experimental analysis, whether GSCI can affect GI is tested. The p-values of the six dimensions in GSCI show significance, indicating that GSCI directly impacts GI. When testing whether there are mediation and moderation effects, Paths 1-3 are all significant, and the confidence interval is [-0.424, -0.07], which does not include 0. KS has a partial mediation effect between GSCI and GI. The p-value of GSCI*EU is 0.004, which is less than 0.05 and is significant, indicating that the EU plays a moderating role between GSCI and GI.